Evaluation and management of hip pain: The Emerging role of hip arthroscopy - Larson, C. M.; Swaringen, J.; Morrison, G. (The Physician and Sportsmedicine, 2005)
Hip arthroscopy is increasingly used as a tool for evaluating and managing painful hip in active patients. The complex anatomy of the lower back, abdomen, pelvis, and upper thigh can make the diagnosis challenging. A thorough history and physical examination in addition to specific imaging modalities can verify the presence or absence of various intra-and extra-articular disorders of the hip. Although hip pain in athletes is often managed conservatively, specific disorders and injuries are appropriately and successfully treated with hip arthroscopy.